Perancangan Ulang Alat Bantu Penghitung Dop Berdasarkan Anthropometri dengan Analisis RULA - Rahmaniyah Dwi Astuti (Performa: Media Ilmiah Teknik Industri, 2010)
Shuttlecock consists of two parts that are dop and feather. Dop is part of the shuttlecock-shaped half-sphere which is at the end of the shuttlecock. In a dop small industry of Mr. Sumeri in Jagalan have four main activities in the production processes that are dop pressing, dop cutting edge, put a cloth on the end of the dop and counting. The calculation activity done during the change of dop production process, after buying dop that has not been coated nylon fabric and when there is order. Calculation is needed to determine how many dop that has been processed by the workers as the basis for the calculation of the workers earned wages each week. Calculation activity can disturb the workers because they have to use work time to calculate the dop that has been processed and waiting for the counting is complete. In this study is conducted redesign tool of dop counter based on anthropometri with RULA analysis. The purpose of this research is to produce a dop counter so that it can improve ergonomic working posture. The tool is designed as dop counter with anthropometri approach to retrieve data anthropometri 3 workers in the dop industry of Mr. Sumeri. By RULA method for dop calculating, the activity use thier upper body is more dominant which it aims to investigate the working environment that is not ergonomic in the human upper body. The result based on RULA is posture of workers can work longer when using the tool indicates a high risk level. Furthermore redesigned tool of dop counter provides working posture at the lower level of risk and the time counsumed by dop calculation process using a new tool as 1 minute per 20 dozen dop. This research produces dop counter-dimensional with high, wide and long of dop counter, respectively 67 cm, 63 cm and 80 cm; dimensions of the dop channel are length: 84 cm, width: 52 cm and height: 20 cm; dimension counter are length: 48 cm, width: 40 cm and the dimensions of the hole are length: 3.5cm, width: 3.5 cm and height: 6 cm. The total cost of making the new light bulb counter is Rp 266,000.00.